The Role of Color in Influencing Consumers - R. Ganesh (International Journal of Behavioral Sciences, 2024)
Marketers have long used color's ability to attract customers' attention. Products with attractive packaging will definitely attract the attention of customers and differentiate themselves from other products on the shelf. Many studies have shown that color dulling can occur when the representation of color relationships is not consistent. Thus, the purpose of this study is to comprehend how color influences consumers. In order to find out the participants' preferred colors, an online survey was sent to them. It was determined that people liked yellow the least and blue the most. There are significant differences in gender selection. The results showed that color influences consumers' decision-making process and brand recall. The study also found significant differences among participants in their purchase of warm and cool colors, as well as warm and neutral colors. Numerous studies indicate that inconsistency in depicting color relationships can lead to color dulling. Thus, this research was conducted to explore how color impacts consumer behavior. An online survey was used to gather data on participants' color preferences, revealing a distinct favoritism for blue over yellow, with notable variations based on gender. The findings confirm that color plays a crucial role in shaping consumer decision-making and memory recall. Significant differences were also observed in preferences for warm versus cool colors, as well as between warm and neutral hues. Furthermore, the study highlighted age-related differences in color preferences, with younger individuals gravitating towards brighter, more vivid colors, while older participants showed a preference for more muted shades. These insights suggest that marketers need to account for both demographic characteristics and color perceptions to effectively target their audience and boost the visibility and appeal of their products.
Keywords: color preferences; color psychology; consumer behavior; cultural influence; emotional response; purchasing decisions